Influência de um fragmento florestal sobre as comunidades de macroinvertebrados de um córrego tropical degradado - Suga, Cristiane Midori (2012)
Land use changes have resulted in large environmental impacts, and in agricultural landscapes sometimes only forest fragments remain. However, riparian forest remnants can influence positively stream water quality, and serve as refuge to aquatic species sensible to deforestation. We evaluated if the presence of a riparian forest remnant influences the structure and composition of macroinvertebrate communities in a rural stream in southeastern Brazil. We sampled three reaches upstream (within abandoned sugarcane cultivation), one at the edge and nine downstream the remnant edge, until 600 m inside the forested area, using leaf litter bags. The abundances of Elmidae, Chironomidae, and total macroinvertebrates increased along the forest remnant, whereas the abundance of Baetidae, proportion of Ephemeroptera, Plecoptera and Trichoptera (EPT), EPT/Chironomidae ratio, and taxon richness and diversity decreased. EPT taxon richness and abundance did not vary along the forest remnant. Reaches upstream the remnant have herbs and grasses that increased microhabitat availability and, consequently, the diversity and taxon richness in this degraded areas. Increases in abundances of Chironomidae and total macroinvertebrates within the forested area can be related to moderate increases in nutrient concentrations or availability of high quality leaf litter patches. Forest remnants can influence macroinvertebrate communities, although variation in their responses can be related to local agricultural practices and land use at the watershed scale. Forest fragments are important in maintaining water quality in agricultural landscapes, deserving special attention in watershed management projects and more commitment from the authorities to comply with environmental laws, aiming to protect and recover permanent preservation areas (PPA) in irregular situation.